2014
DOI: 10.1021/jp501846f
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Reaction of Nanoscale Zerovalent Iron with Water: Mechanism and Kinetics

Abstract: Nanoscale zerovalent iron (nZVI) is commonly used in advanced groundwater remediation processes. Here, we present a combined experimental and computational approach to elucidate the mechanism and kinetics of the reaction of nZVI with water under anaerobic conditions, which represents the basic reaction controlling the stability of nZVI in groundwater. The reaction kinetics was monitored at temperatures of 25 and 80 °C by 57 Fe Mossbauer spectroscopy on frozen dispersion samples. The experimentally determined r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 52 publications
1
90
1
Order By: Relevance
“…On the one hand it has been clearly demonstrated that long-term water exposure decreases the reactivity of nZVI against a wide range of pollutants due to the growing of the oxide/hydroxide shell [11,13,18,[25][26][27][28][29], which leads to a passivation of the particles and it is commonly known as water aging [30].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand it has been clearly demonstrated that long-term water exposure decreases the reactivity of nZVI against a wide range of pollutants due to the growing of the oxide/hydroxide shell [11,13,18,[25][26][27][28][29], which leads to a passivation of the particles and it is commonly known as water aging [30].…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solutions, nZVI reacts with water and dissolved oxygen to form ferrous iron and hydrogen gas (Equations 3.1 -3.2). (Nurmi et al, 2005, Filip et al, 2014. Magnetite is one of the main oxidized forms of iron formed on the surface of nZVI, but it is not considered a strong reductant for reductive dechlorination of organic compounds (Lee and Batchelor, 2002) Thus far, nZVI has been unable to dechlorinate 1,2-DCA Zhang, 2005, Song and.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 The formation of Fe 3 O 4 in pure water is thermodynamically possible; the electrochemical equilibrium potential of the metal oxidation half reaction of Fe(OH) 2 53,54 who suggested that lepidocrocite (γ-FeOOH) is formed via oxidation of Fe II (aq) and subsequent precipitation. It may be possible that dissolved ferrous ions can be oxidized in the solution phase.…”
Section: Proposed Mechanism For Evolution Of Cs Corrosionmentioning
confidence: 99%